Factors Affecting Working Capital Credit Decisions in Micro, Small and Medium Enterprises (MSME) at BMT Muamalat Semarang - Umar Chadhiq; Nanang Yusroni (Journal of Wetlands Environmental Management, 2022)
In general, the credit period is a reflection of the credit risk that may arise provided by the bank to MSMEs to return principal and interest on the loan. The longer the credit term, the higher the risk that may arise, then the bank will charge higher interest compared to short-term credit. The existence of the phenomenon then the method to answer the above problems in the form of field surveys using questionnaires to 93 respondents in the form of Likert scale. The analysis technique used was multiple linear regression analysis. Result showed that MSMEs can manage debt or credit management from BMT Muamalat for its business activities. Each MSMES has different managing abilities. What is meant by the ability to manage credit here is the ability to manage his business after obtaining loan funds from BMT Muamalat.